Pre-hospital emergency anaesthesia in 2025: ten years on from the modification of induction regimes - Mark Hodkinson; David Zideman; Kurtis Poole (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Pre-hospital emergency anaesthesia has become a common intervention in pre-hospital emergency medicine. Induction regimes have been modified significantly in the last decade largely guided by medical literature. A Thames Valley Air Ambulance working group have reviewed contemporary literature, developing updated guidelines on the induction and maintenance of pre-hospital emergency anaesthesia. The choice of agents remains unchanged, but there is a growing emphasis on providing a more tailored anaesthetic considering the patient’s frailty, background history and presenting physiology. Additional research into the optimal dose and combination of drugs is warranted, together with further exploration of patient’s physiological responses to pre-hospital anaesthesia.